تتبع الرخص وأثره في الفقه الإسلامي - ثريا محمد سعيد (Kulliyah Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2005)
This research studied the optimal concessions (al-rukhas) of different juristic schools of thoughts (al-madhāib), adopting an analytical-comparative method. It started by defining the term (al-rukhas) and exploring the main reasons that led to their earlier definitions. The study looked at scholars’ views regarding its authenticity, and how the question of fabrication came about among the different (al-madhāib). The study adopted a comparative analytical method to analyze Qur’anic verses related to this particular topic and reliable classical juristic writings. The study came up with several results. One of the important results is the emphasis on the permissibility of the idea of looking for the optimal concessions to be acceptable if certain conditions and criteria are duly fulfilled. This notion is based on the basic concept saying that it is not compulsory for the adults (al-mukallafūn) to follow particular school of juristic thought, since the schools will be subjected to changes. The study also concluded that the reform of Islamic laws as well as juristic thoughts in the modern era can not oppose the prophet traditions (al-hadīth) related to the idea of religious reformation as long as that reformation does not atter the fundamentals of Islam.